Modelling and optimization of a two phase system for the separation of equol enantiomers by recycling high-speed counter-current chromatography. Issue 15 (31st August 2015) - Tang, Kewen; Sun, Genlin; Zhang, Panliang; Yang, Weijun; Zhou, Congshan; Yang, Changan
Graphical abstract: Abstract: Enantiomers of equol were separated by recycling high-speed counter-current chromatography (HSCCC) using hydroxypropyl-β-cyclodextrin (HP-β-CD) as the chiral selector. As a key issue for the HSCCC process, the two phase solvent system was selected. The influence of the type and concentration of the chiral selectors, pH value of the aqueous solution as well as the temperature on distribution of the enantiomers were investigated. A mathematical model was established to simulate the influence of the important factors on the distribution of the enantiomers in the two-phase system. It was found that model predictions were in good agreement with the experimental results. The model was further used for optimizing the two-phase system. The optimized two-phase solvent system was composed of an n -hexane–ethyl acetate–0.1 mol/L phosphate buffer solution with pH = 6.0 (3:7:10, v/v/v) while concentration of HP-β-CD was 0.1 mol/L. Based on the optimized system, HSCCC separation process was performed and a recycling elution mode was employed to enhance the separation ability. Complete separation of 20 mg of equol enantiomers was finally achieved, and 8.6–9.0 mg of ( R )-equol and ( S )-equol with 98.5% purity and 86–90% recovery were obtained.